The Income-Expenditure-Saving Analyses of the University Students - Jalil, Norasibah Abdul; Rambeli, Norimah; Hashim, Asmawi; Hashim, Emilda; Zulkifli, Normala (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this study are; i) to identify the students’ sources of income and students’ income level, ii) to explore students’ expenditure pattern and student’s expenditure level, and iii) to measure students saving status. 301 university students participated in this study. The instrument used for data collection is questionnaire set, which are constructed by using Google form and distributed through link sharing. The data are analysed by using SPSS version 23 software. The findings of the analyses provide indication that students’ sources of income mainly come from government’s loan (PTPTN) and parents. The average income level of the students is RM539.70. For expenditure analysis, the main expenditure items are; food and beverages, and accommodation. The students’ average expenditure level is 915.94 (with average expenditure level on necessity items is 774.04). With the income and expenditure levels, the calculated saving level is -202.55 (considering expenditure on necessities only) and -344.45 (total expenditures). Based on this finding, we may conclude, the amount of money obtained by the students is relatively low, and insufficient even to cover their expenditure on necessity items. In relating to this, it is recommended the existing amount of PTPTN loan provided by the government to be review, and to be linked with parental income in order to guarantee the welfare and the wellbeing of the student.